449 Prevalence of Allergy among University Students, Ajman, Uae. (October 2012) - John, LJ; Arifulla, M; Sreedharan, J
Abstract : Background and Aims: Urbanization and globalization in UAE has resulted in drastic environmental changes and increase in allergens present in the environment and also the prevalence of allergies. Hence, this study aimed to assess the prevalence of allergies among undergraduate students of Gulf Medical University. Methods: This cross-sectional survey was carried out among undergraduate students of Gulf Medical University. A self administered questionnaire was used as research instrument for data collection. The demographic data and allergy characteristics were collected and analyzed using SPSS version 19. Descriptive and analytic statistics were performed. Results: A total of 255 students were included (31% males, 69% females). The commonest allergies among university students were allergic rhinitis 120(47%); allergic conjunctivitis 104(40.8%), atopic dermatitis 89(34.9%) and bronchial asthma 31(12.2%) in the rank order. Positive family history of allergies was reported by 62(24.3%) for atopic dermatitis, 39(15.3%) for allergic rhinitis and 33(12.9%) for allergic conjunctivitis. The allergies were common among Pakistani and African nationals. Allergic rhinitis was also frequent among Emiratis. Allergies were common during months of January and December. Allergies associated with pollen, food and drug were less frequent. The distribution of allergies based on gender revealed female preponderance in all the types of allergy. Students with allergies reported interference with their daily activities, academic activities, social and extra-curricular activities. Conclusions: Overall higher prevalence of allergies noted among students especially the African and Pakistani students. Adequate preventive strategies should be initiated to curb this rising prevalence of allergies.